Ensuring the Global Availability of High-quality Dental Restorative Materials. (November 2013) - Ferracane, J.; Fisher, J.; Eiselé, J.L.; Fox, C.H.
The Minamata Convention, a global legally binding instrument (treaty) on mercury, has been the catalyst for the emerging agenda on global dental materials research. If the current and future challenges of oral health maintenance and healing on a global scale are to be met, a logical and effective research agenda for the discovery and introduction of new, environmentally sustainable, dental materials must be developed through a coordinated effort involving materials scientists, dental clinicians, representatives of industry, members of regional and national regulatory bodies, and advocacy from research organizations. For universal impact, this agenda should be created with awareness of several important ongoing initiatives, such as the WHO non-communicable diseases action plan, the UN sustainable development agenda, and the IADR Global Oral Health In Inequalities Research Agenda (GOHIRA). A significant contributor to this cause is the FDI and its membership, who, through their Vision 2020 initiative, acknowledge their role and responsibility in globally preventing and managing dental disease and providing leadership to the profession in terms of information dissemination and affecting change. Dental researchers also have an obligation to advocate for appropriate funding to match the identified research needs, thus enhancing the possibility that key decision-makers will provide the needed support to achieve the research agenda agreed upon by this diverse group of stakeholders.